Charge carrier dynamics and reaction intermediates in heterogeneous photocatalysis by time-resolved spectroscopies. (30th June 2022) - Ma, Jiani; Miao, Tina Jingyan; Tang, Junwang
Abstract : Time-resolved absorption and IR spectroscopies can explore the charge dynamics and kinetics of heterogeneous photocatalytic systems and elucidate the correlation between materials design, charge carrier behavior, and photocatalytic activity. Abstract : Sunlight as the most abundant renewable energy holds the promise to make our society sustainable. However, due to its low power density and intermittence, efficient conversion and storage of solar energy as a clean fuel are crucial. Apart from solar fuel synthesis, sunlight can also be used to drive other reactions including organic conversion and air/water purification. Given such potential of photocatalysis, the past few decades have seen a surge in the discovery of photocatalysts. However, the current photocatalytic efficiency is still very moderate. To address this challenge, it is important to understand fundamental factors that dominate the efficiency of a photocatalytic process to enable the rational design and development of photocatalytic systems. Many recent studies highlighted transient absorption spectroscopy (TAS) and time-resolved infrared (TRIR) spectroscopy as powerful approaches to characterise charge carrier dynamics and reaction pathways to elucidate the reasons behind low photocatalytic efficiencies, and to rationalise photocatalytic activities exhibited by closely related materials. Accordingly, as a fast-moving area, the past decade has witnessed an explosion in reports on charge carrier dynamics and reaction mechanisms on a wide range of photocatalytic materials. This critical review will discuss the application of TAS and TRIR in a wide range of heterogeneous photocatalytic systems, demonstrating the variety of ways in which these techniques can be used to understand the correlation between materials design, charge carrier behaviour, and photocatalytic activity. Finally, it provides a comprehensive outlook for potential developments in the area of time-resolved spectroscopies with an aim to provide design strategies for photocatalysts.